Ten-year experience of whole lung lavage in pediatric Pulmonary Alveolar Proteinosis - Nickel, Katja; Schütz, Katharina; Carlens, Julia; Grewendorf, Simon; Wetzke, Martin; Keil, Oliver; Dennhardt, Nils; Rigterink, Vanessa; Köditz, Harald; Sasse, Michael; Happle, Christine; Beck, Christiane E.; Schwerk, Nicolaus (Klinische Pädiatrie, 2024)
Background Pulmonary Alveolar Proteinosis (PAP) is extremely rare and can be caused by hereditary dysfunction of the granulocyte macrophage colony-stimulating factor receptor (GM-CSF) receptor, autoantibodies against GM-CSF, or other diseases leading to alveolar macrophage (AM) dysfunction. This leads to protein accumulation in the lung and severe dyspnea and hypoxemia. Whole lung lavage (WLL) is the first line treatment strategy.Methods Here, we present data from more than ten years of WLL practice in pediatric PAP. WLL performed by the use of a single lumen or double lumen tube (SLT vs. DLT) were compared for technical features, procedure time, and adverse events.Results A total of n=57 procedures in six PAP patients between 3.5 and 14.3 years of age were performed. SLT based WLL in smaller children was associated with comparable rates of adverse events but with longer intervention times and postprocedural intensive care treatment when compared to DLT based procedures.Discussion Our data shows that WLL is feasible even in small children. DLT based WLL seems to be more effective, and our data supports the notion that it should be considered as early as possible in pediatric PAP.Conclusion WLL lavage is possible in small PAP patients but should performed in close interdisciplinary cooperation and with age appropriate protocols.
Keywords: Whole lung lavage; single lung ventilation; bronchoscopy; Pulmonary Alveolar Proteinosis; pediatric anaesthesia